Modeling of structure and failure processes of granular composites - Ilinykh, Artem Valerievich; Vildeman, Valeriy Ervinovich (Computational Continuum Mechanics, 2012)
Mathematical models of granular structurally inhomogeneous media, deformation processes, and damage accumulation and failure have been developed. The mechanisms of defective structure evolution are determined by computational experiments. The relationships between the effective strength and deformation properties of granular composites and their structural parameters are obtained. Based on the calculation and experimental data obtained in this study, a hypothesis for the existence of large-scale effects in the post-critical stage of deformation is proposed.
Keywords: numerical modeling; granular composites; damage accumulation and failure; large-scale effect; post-critical stage